Avaliação do látex de Jatropha curcas L.: propriedades físicas, químicas e biológicas - Pereira, Illana Reis (2017)
Jatropha curcas L, popularly known as physic nut, is a shrub of the Euphorbiaceae family, with multiple uses. The objectives of this work were: 1) reporting the main trends and gaps of global scientific literature about J. curcas L species through a scientometric analysis; 2) performing the phytochemical characterization of the latex and identified its compounds; 3) evaluating the genotoxic and antigenotoxic activity of latex. For the scientometric analysis, the ISI - Web of Knowedge data base was used and the search was made using the words "Jatropha curcas or "physic nut". The methodology employed on the phytochemical characterization was: secondary metabolites identification, pH determination, elemental analysis, infrared spectroscopy and thermogravimetric. For the evaluation of the genotoxic and antigenotoxic potential the micronucleus test was used in bone marrow cells of mice treated with doses of latex and doxorubicin. As result it was observed a continuous increase in both quantitative and qualitative parameters in the studies about J. curcas. In addition, the main trends in the studies of J. curcas are related to the production of biofuels, and the main gaps are related to forestry and sustainability, animal nutrition and genetic improvement. Another problem identified was the lack of commercial seeds, which makes it difficult to plant large areas. India, Brazil and China together accounted for 55% of the knowledge on this species. Through the phytochemical characterization, it was possible to identify the secondary metabolites anthraquinones heterosides, flavonoids and tannins. Also it was verified that the latex is composed of 40% of carbon, 4% of hydrogen and 1% of nitrogenand other 54% remaining were not identified. When compared to latex of mangabeira, it was observed that the J. curcas latex had low amount or absence of 1.4 polyisoprene and was less thermally stable. The results obtained by the in vivo micronucleus test showed that the latex has genotoxic activity at concentrations of 50 and 100 mg / kg b.w. and cytotoxic activity at all concentrations studied. In relation to antigenotoxic activity, latex inhibited DNA damage when administered together with the doxorubicin. The conclusions obtained in this study were: 1) in spite of the increase in the number of articles on J. curcas, many countries stopped cultivating it mainly due to lack of information about the species; 2) phytochemical analyzes identified in the latex the anthraquinones heterosides, flavonoids and tannins, which have different biological functions and are substances of pharmacological interest; 3) a significant difference was observed between the components of the J. curcas biofilm and the mangabeira biomembrane, which could be observed in the alterations of its elastic properties and probably in its biological applications; 4) J. curcas latex shows genotoxic and cytotoxic activity when given alone to mice, but they have antagonistic effect and antigenotoxic activity when administered simultaneously as drug doxorubicin. These results show that care must be taken with drug interactions, and that the empirical use of J. curcas latex by the population can cause serious damage to health.